Multi-element analysis of crude oils using ICP-QQQ-MS. (January 2017) - Walkner, Christoph; Gratzer, Reinhard; Meisel, Thomas; Bokhari, Syed Nadeem Hussain
Highlights: Measurement of minor, trace and ultra-trace elements in crude oils by ICP-MS/MS. Enhanced polyatomic interference removal by controlled reaction cell chemistry. 25 elements, including P and S, accurately quantified in one run. High sensitivity detection of ultra-trace elements without prior evaporation. The method can easily be extended to include further elements. Abstract: Determination of trace element contents in crude oils constitutes a powerful geochemical tool, complementing organic geochemical analyses and allowing a deeper insight into the processes of oil generation, migration and maturation. Inductively coupled plasma mass spectrometry (ICP-MS) has been widely applied to trace element determination in petroleum samples due to its low detection limits and fast multi-element capability. However, quantification of several elements by quadrupole-based ICP-MS is hampered by low sensitivity due to high ionisation energy, severe polyatomic interferences and/or low abundance. In the present contribution an ICP tandem mass spectrometer (ICP-MS/MS), or triple quadrupole ICP-MS (ICP-QQQ-MS) has been used to overcome these limitations. Prior to analysis, samples were subjected to high pressure acid digestion, allowing external calibration by means of aqueous standards. 25 elements, including P, S, the first-row transition metals, As, Se, Re, Pb and U, could be quantified in one measurement. Polyatomic interferences on the lighter elements could be removed by reaction of the target ions with O2 or NH3 in the collision/reaction cell of the ICP-MS/MS. The accuracy of the analytical method was assessed by the analysis of the standard reference materials NIST SRM 1634c (trace elements in fuel oil) and 1084a (wear-metals in lubricating oil). The measurement procedure was applied to the analysis of crude oil samples from the Alpine Foreland Basin of Austria.